Community development projects in rural China : an analysis of processes and changes - Zhang, Jun; Ahmad, Mokbul Morshed; Soparth Pongquan; Routray, Jayant Kumar; Ford Foundation (Pathum Thani, Thailand : Asian Institute of Technology, 2009)
This research is a comparative analysis of processes and changes between community-driven development project and multi-sector project in rural China. Two cases from Baishui county are compared in a variety of processes, i.e. project inputs, activities and outputs. By using data from government documents, CDD program monitoring and evaluation reports, household survey, and interviews with county program officials, NGO staff and community members, I identified the major changes of the CDD program brought to local institutions and community members' participation. Moreover, the major similarities and differences of the two approaches in community management are identified in this research. As an input, institution building formulates community members' participation in the process of project. Community members' participation contributes much trust and commitments to community self-management. In order to provide reference for the institutional arrangement of poverty alleviation and public service, policy recommendations are given for the future plan of community development program
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Regional and Rural Development Planning
Thesis (M.Sc.) - Asian Institute of Technology, 2009
Keywords: Rural development -- China